A mechanical evaluation of pre-tapped and self-tapped screws in small bones - Bell, J. C.; Ness, M. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
The purpose of this study was to compare the holding powers of 2.7 mm pre-tapped and self-tapped screws placed closely together and tightened in small bones. Pairs of metatarsals were collected from healthy, skeletally mature Greyhounds and part of a 2.7 mm dynamic compression plate was fixed to the dorsal surface of each bone using three 2.7 mm screws. Identical screws were used throughout but only one of each pair of bones had threads pre-cut using a tap prior to insertion. All of the screws were tightened before the constructs were mounted in a materials testing machine and the centrally placed screw was loaded incrementally until failure. Load-deformation curves were plotted and yield point, ultimate load to failure, stiffness and energy prior to yield point were measured. Mean values were recorded for each parameter and Student's T-test was used to test the null hypothesis that there is no difference in holding power between pre-tapped and self-tapped screws. Significant mechanical differences were not found between pre-tapped and self-tapped screws placed closely together and tightened into small bones. Self-tapped screws can be considered for use in small animal surgery even when multiple screws are to be placed closely together in relatively small pieces of bone.
Keywords: Screws; pre-tapped; self-tapped